【判断题】ln(x) / ln(y) = ln(x) - ln(y) (True 正确 or False 错误)
【判断题】ln(x) / ln(y) = ln(x) - ln(y) (True 正确 or False 错误)
设\(z = {\log _y}x\),求\({z_x}\)= A: \({1 \over {y\ln x}}\) B: \({1 \over {\ln x}}\) C: \({1 \over {x\ln y}}\) D: \({1 \over {ln y}}\)
设\(z = {\log _y}x\),求\({z_x}\)= A: \({1 \over {y\ln x}}\) B: \({1 \over {\ln x}}\) C: \({1 \over {x\ln y}}\) D: \({1 \over {ln y}}\)
已知z=3x²+x-y+ln(x²+y²)则在(1,1)处全微分 dz=____。
已知z=3x²+x-y+ln(x²+y²)则在(1,1)处全微分 dz=____。
函数\( y = {e^x} - 1 \)的反函数是( )。 A: \( y = \ln x + 1,x > 0 \) B: \( y = \ln (x + 1),x > - 1 \) C: \( y = \ln x - 1,x > 0 \) D: \( y = \ln (x - 1),x > 1 \)
函数\( y = {e^x} - 1 \)的反函数是( )。 A: \( y = \ln x + 1,x > 0 \) B: \( y = \ln (x + 1),x > - 1 \) C: \( y = \ln x - 1,x > 0 \) D: \( y = \ln (x - 1),x > 1 \)
方程xdy/dx=yln(y/x)的通解为()。 A: ln(y/x)=Cx-1 B: ln(y/x)=Cx<sup>2</sup>+1 C: ln(y/x)=Cx<sup>2</sup>+x D: ln(y/x)=Cx+1
方程xdy/dx=yln(y/x)的通解为()。 A: ln(y/x)=Cx-1 B: ln(y/x)=Cx<sup>2</sup>+1 C: ln(y/x)=Cx<sup>2</sup>+x D: ln(y/x)=Cx+1
设\(z = {e^ { { y \over x}}} + {x^y} + {y^x}\),则\({z_x} = \) A: \({1 \over x}{e^ { { y \over x}}} + {x^y}\ln x + x{y^{x - 1}}\) B: \(- {y \over { { x^2}}}{e^ { { y \over x}}} + {x^y}\ln x + x{y^{x - 1}}\) C: \({e^ { { y \over x}}} + y{x^{y - 1}} + {y^x}\ln y\) D: \( - {y \over { { x^2}}}{e^ { { y \over x}}} + y{x^{y - 1}} + {y^x}\ln y\)
设\(z = {e^ { { y \over x}}} + {x^y} + {y^x}\),则\({z_x} = \) A: \({1 \over x}{e^ { { y \over x}}} + {x^y}\ln x + x{y^{x - 1}}\) B: \(- {y \over { { x^2}}}{e^ { { y \over x}}} + {x^y}\ln x + x{y^{x - 1}}\) C: \({e^ { { y \over x}}} + y{x^{y - 1}} + {y^x}\ln y\) D: \( - {y \over { { x^2}}}{e^ { { y \over x}}} + y{x^{y - 1}} + {y^x}\ln y\)
方程xdy/dx=yln(y/x)的通解为()。 A: ln(y/x)=1 B: ln(y/x)=Cx+1 C: ln(y/x)=Cx<sup>2</sup>+1 D: ln(y/x)=Cx<sup>3</sup>+1
方程xdy/dx=yln(y/x)的通解为()。 A: ln(y/x)=1 B: ln(y/x)=Cx+1 C: ln(y/x)=Cx<sup>2</sup>+1 D: ln(y/x)=Cx<sup>3</sup>+1
设\(z = {\log _y}x\),则\({z_y} = { { \ln x} \over {y { { \ln }^2}y}}\).
设\(z = {\log _y}x\),则\({z_y} = { { \ln x} \over {y { { \ln }^2}y}}\).
dy/dx=(x+y)/(x-y)的通解为 A: arctan(u)-0.5ln(1+u)=ln|x|+C B: arctan(u)-0.5ln(1+u^2)=ln|x|+C C: arctan(y/x)-0.5*ln(1+(y/x)^2)=ln|x|+C D: arctan(y)-0.5*ln(x)=ln|x|+C
dy/dx=(x+y)/(x-y)的通解为 A: arctan(u)-0.5ln(1+u)=ln|x|+C B: arctan(u)-0.5ln(1+u^2)=ln|x|+C C: arctan(y/x)-0.5*ln(1+(y/x)^2)=ln|x|+C D: arctan(y)-0.5*ln(x)=ln|x|+C
解方程(x+ycos(y/x))dx-(xcos(y/x))dy=0 A: sin(y/x)=ln|x|+c B: cos(y/x)=ln|x|+c C: sin(y/x)=lnx+c
解方程(x+ycos(y/x))dx-(xcos(y/x))dy=0 A: sin(y/x)=ln|x|+c B: cos(y/x)=ln|x|+c C: sin(y/x)=lnx+c